Antibacterial Activity Test of Acne Patch with the Addition Sea Grapes (Caulerpa racemosa) Extract Against Propionibacterium acnes Bacteria - Muzaki, Fahri; Hasanah, Afifah Nurazizatul; Pratama, Ginanjar (Universitas Gadjah Mada, 2025)
Acne patch preparation is an acne medication that is used topically. Sea grape (Caulerpa racemosa) has the potential to contain antibacterial substances that can be applied to acne patch preparations to suppress the growth of acne-causing bacteria Propionibacterium acnes. The objective of this research is determining the potential of Caulerpa racemosa antibacterial substances applied to acne patch preparations in suppressing the growth of bacteria that cause Propionibacterium acnes acne. The treatment used was the addition of different Caulerpa racemosa extracts (0%, 15%, 20%, and 25%). Parameters observed were pH, antibacterial, irritation, thickness, hedonic, moisture absorption, water absorption, and adhesion. The analysis showed that adding Caulerpa racemosa extract had a significant effect (P<0.05) on antibacterial activity. The addition of extract with a concentration of 25% is the best treatment compared to other treatments, with an antibacterial activity value of 5.25 ± 0.35 mm with a weak inhibition zone category, pH 5.92±0.04, non-irritating, thickness 0.54±0.02 mm, hedonic getting somewhat like value (appearance, aroma, and texture), moisture absorption 4.47±0.03%, water absorption 1.16±0.02%, and adhesion 231.24±0.08 seconds.